2021
DOI: 10.1002/tox.23298
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin ameliorates injury and inflammatory response of LPS‐stimulated WI‐38 cells via modulating the miR‐489‐3p/MAP2K1 axis

Abstract: Pneumonia is an inflammatory disease induced by infection with different pathogens. Currently, multiple preclinical studies have revealed that shikonin, a natural naphthoquinone, can mitigate lipopolysaccharide (LPS)‐induced inflammation, but its underlying mechanism in pneumonia remains unknown. This research was designed to explore the function and regulatory mechanism of shikonin in LPS‐induced cell injury and inflammation in WI‐38 cells. In‐vitro model of pneumonia was constructed by treating WI‐38 cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Overexpression of TPTEP1 inhibited the viability and proliferation of HRVECs, and suppressed oxidative stress, suggesting that TPTEP1 could be a potential target for DR. Additionally, further study showed that TPTEP1 could directly target miR-489-3p. MiR-489-3p is related to the regulation of gastric cancer (Mao et al, 2021) and inflammatory response (Wang et al, 2021;Ye et al, 2021). However, miR-489-3p is rarely studied in the development of DR/The reports on the roles of miR-489-3p in DR are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TPTEP1 inhibited the viability and proliferation of HRVECs, and suppressed oxidative stress, suggesting that TPTEP1 could be a potential target for DR. Additionally, further study showed that TPTEP1 could directly target miR-489-3p. MiR-489-3p is related to the regulation of gastric cancer (Mao et al, 2021) and inflammatory response (Wang et al, 2021;Ye et al, 2021). However, miR-489-3p is rarely studied in the development of DR/The reports on the roles of miR-489-3p in DR are limited.…”
Section: Discussionmentioning
confidence: 99%
“…LPS was reported to be used in the induction of inflammatory responses in a variety of human cells. [33][34][35] We used LPS to induce mast cell inflammatory responses. Our data showed that apigenin suppressed the LPS-induced decrease in cell viability and increase in cell apoptosis and the levels of inflammatory factors (including IL-6, TNF-α, and IL-1β).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that apigenin treatment blocked the production of β‐hexosaminidase and histamine induced by compound 48/80 in mast cells. LPS was reported to be used in the induction of inflammatory responses in a variety of human cells 33–35 . We used LPS to induce mast cell inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…24 LPS is a vital constituent of the endotoxin secreted by gram-negative bacilli and is the leading cause of ALI. 20,25 Epigenetic modifications are involved in macrophage activation and differentiation. 26 Our results suggested that LPS-induced Macrophage is a central mediator in LPS-induced inflammatory response, both in the promotion and resolution of inflammation 27 via its dominant M1 or M2 phenotype in ALI.…”
Section: Discussionmentioning
confidence: 99%
“…ALI is characterized by the infiltration of excessive inflammatory cells 24 . LPS is a vital constituent of the endotoxin secreted by gram‐negative bacilli and is the leading cause of ALI 20,25 . Epigenetic modifications are involved in macrophage activation and differentiation 26 .…”
Section: Discussionmentioning
confidence: 99%